RATE OF HOSPITAL-ACQUIRED INFECTIONS AMONG INPATIENTS AT BINH TAN HOSPITAL, HO CHI MINH CITY. (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the rate of hospital-acquired infections (HAIs) and associated factors at Binh Tan Hospital in 2022.Subjects and Methods: A cross-sectional study was conducted on 424 inpatients across eight clinical departments at Binh Tan Hospital between June and December 2022 (patients hospitalized for ≥2 days). Data were collected via electronic medical records and clinical examinations; HAIs were diagnosed according to Decision 3916/QĐ-BYT. Data were analyzed using Stata 20.0 software, employing Chi-square or Fisher's exact tests, with statistical significance set at p
Keywords: Hospital-acquired infections, surgical site infections, infection control